Pengertian Maqoshid Syari'ah - Kariimah, Muhimmatul; Sofia, Lia (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
The purpose of determining law or often known as maqashid al-syari‟ah is one of the important concepts in the study of Islamic law. Because of the importance of maqashid al-shari'ah, legal theorists make maqashid al-shari'ah something that must be understood by mujtahid who performs ijtihad. In relation to methods or ways to find wisdom and the purpose of law-making, there are at least three ways that have been taken by scholars before al-syatibi Modern and contemporary Muslim scholars introduced the new concept and classification of maqashid al-shari'ah by including the new dimensions of maqashid, namely national economic development as an integral part of the goals of sharia. Develop the terminology of "traditional" maqashid al-shari'ah, in order to correct the shortcomings in the concept of "traditional" maqashid al-shari'ah. The theory of maqashid al-Shari'ah is also very relevant to the establishment of a binding and coercive national law. Maqashid al-shari'ah is in harmony with one of the purposes of law, namely utility.